HUBUNGAN PANJANG BADAN LAHIR TERHADAP PERKEMBANGAN ANAK USIA 12 BULAN - Fitrah Ernawati; Sri Muljati; Made Dewi S; Amalia Safitri (Persagi, 2014)
ABSTRACTGrowth retardation such as stunting among children under five years old in Indonesia was serious. Stunting have negative effects on mental development especially in children under five years old. We conducted a 24 months follow up study at 10 primary health care (Puskesmas) in Bogor District. Subjects of the study were children in their gestational stage which were followed up for 12 months after birth. The indicator of stunting was measured by Z-score of height for age (HAZ), while child development was assesed using Bailey’s test III. Spearman correlation is used in data analysis. The result of the study showed that 9.5 percent children were born with low birth weight (birth weight < 2500 gr) and stunted ( body length < 48 cm). There was an association between birth length and motoric as well as socio-emotional development since birth (0 month old) (rho=0,33; p=0,004 for motoric, and rho=0,244 ,p=0,036 for socio-emotion). On the other hand, significant correlation between birth length and linguistic development only showed up at one month old (rho=0,29, p=0,031 ), and the correlation with cognitive development showed up at two month old (rho=0,031,p=0,0011). The linguistic abilities of a stunted child were lower than that of a normal child. The duration of breast feeding also had a role in the development of these children. Length of child at birth has an effect on child development.Keywords: birth length, birth weight, child developmentABSTRAKPendek (stunting) adalah gangguan pertumbuhan pada anak balita di Indonesia yang perlu mendapat perhatian serius. Salah satu dampaknya adalah stunting, terutama pada anak usia kurang dua tahun yang mengakibatkan penurunan tingkat kecerdasan. Artikel ini menggunakan data penelitian yang dilakukan di 10 puskesmas di Kabupaten Bogor, selama 48 bulan dengan disain follow up study. Partisipan dalam penelitian ini adalah bayi yang diikuti mulai dari dalam kandungan sampai bayi berusia 12 bulan. Data yang diolah adalah data panjang badan, umur dan tingkat perkembangan. Data stunting didapatkan berdasarkan z-skor tinggi badan terhadap umur, sedangkan data perkembangan anak didapatkan mengguankan Bailey’s Test III. Analisis data menggunakan uji korelasi Spearman. Hasil penelitian menunjukkan sebanyak 9,5 persen bayi dengan berat badan lahir rendah (BBLR) dan 22 persen stunting. Nilai z-skor panjang badan terhadap umur pada bayi baru lahir berkolerasi dengan perkembangan motorik dan sosial emosi sejak bayi berumur nol bulan, yaitu rho=0,33; p=0,004 untuk motorik dan rho=0,244 dengan p=0,036 untuk sosial emosi. Sedangkan korelasi terhadap perkembangan bahasa baru tampak pada saat bayi berumur satu bulan yaitu rho=0,29 dengan p=0,031 dan korelasi terhadap perkembangan kognitif terjadi pada usia dua bulan rho=0,318 dengan p=0,011. Pada anak lahir stunting median perkembangan bahasa lebih rendah dibandingkan kelompok yang normal. [Penel Gizi Makan 2014, 37(2): 109-118]Kata kunci : stunting, status gizi, perkembangan anak